Screening of steroid 5α-reductase inhibitory activity and total phenolic content of Thai plants - Thapana Kumar (2018)
Steroid 5α-reductase is the enzyme responsible for changing androgen testosterone into the more potent androgen dihydrotestosterone (DHT). Overexpression of DHT can cause many disorders including androgenic alopecia and benign prostatic hypertrophy (BPH). The aim of this study is to determine which plants possess 5α-reductase inhibitory activity, and to evaluate the correlation between 5α-reductase inhibitory activity and total phenolic content of these plants. Ten kinds of Thai plants were collected from local areas and extracted with 95% ethanol. The yields of ethanolic extracts of these plants ranged from 2.22 to 16.05%, dry weight. In the present study the ability of the extracts to inhibit 5α-reductase enzyme has, for the first time, been calculated as finasteride equivalent 5α- reductase activity (FEA) value (mg finasteride per 1 g extract). FEA values are easier to understand and to compare their activity. FEA values of the extracts ranged from 5.56 to 17.59 mg finasteride per 1 g extract. The highest FEA value was found in Ocimum basilicum L. The red strain of Oryza sativa L. was the second most potent 5α-reductase inhibitor, with FEA value of 16.72. Total phenolic content of the extracts ranged from 32.00 to 370.85 mg gallic acid equivalent per 1 g extract. There was no correlation between 5α-reductase inhibitory activity and total phenolic content. Phytochemicals other than phenolic compounds may play an important role in enzyme inhibition. As the usual dosage regimen of finasteride for treating androgen-related disorders is 1 to 5 mg/d, regular intake of these fresh plants or their extracts may be beneficial in health promotion, prevention or treatment effect. ©2011 Academic Journals.